Computer programmer - Waller T; South Africa; Nafte Debbie (South Africa: Awareness Publishing Group (Pty) Ltd, 2010)
An introduction to the job of Graphic Computer programmer, Describing the work of a programmer, the skills and personal qualities required, school subjects that are helpful, and the training and opportunities that are available, the book can help learners to decide if this is a suitable career for them.
Juniour Non-Fiction -; Juvenile Literature